Selective laser melting 3D printed thermal shield metamaterial structure. Issue 3 (April 2021) - Deng, Tianxiang; Li, Bo
Abstract: Due to ingenious design and elaborate construction of artificial structures, thermal metamaterials commonly possess extraordinary properties beyond natural materials under the conventional heat transfer conditions. Based on the transformation thermodynamics theory and the effective medium theory, in this paper, a plane-structure thermal shield aiming to manipulate heat flow was artificially designed and manufactured with the selective laser melting (SLM) 3D printing technology. The well-designed thermal shield allows the heat flow to bypass the central area of the structure for transmission and can be applied for heat protection in industries. Furthermore, the thermal shield metamaterial was fabricated and experimentally tested through the thermal monitor platform. And the experimental findings were in good agreement with the thermal simulation results. Therefore, the research results and the use of SLM 3D printing technology verified the applicability and feasibility of the thermal shield in the fields of thermal engineering and thermal control.